Next Generation Sequencing of Ancient Fungal Specimens: The Case of the Saccardo Mycological Herbarium - Forin, Niccolò; Nigris, Sebastiano; Voyron, Samuele; Girlanda, Mariangela; Vizzini, Alfredo; Casadoro, Giorgio; Baldan, Barbara (Frontiers in Ecology and Evolution, 2018)
Despite their essential role in the environment, the number of known fungal species is still low compared to the recent estimates of the fungal biodiversity, principally because of their often cryptic or ambiguous morphological traits. Recent studies have reported that the number of fungal DNA sequences deposited in public DNA databases and representing correctly a species appears dramatically low (approx. 120,000) when compared with the estimated total number of species (approx. from 2.2 to 3.8 million). Thus, the linkage of curated DNA sequence data to expertly identified voucher specimens is of fundamental importance to fill the present gap between the different sizes of described and sequenced fungal diversity. To this purpose, the mycological herbarium collections are considered an important source for fungal DNA-barcoding, and collection-based sequencing is a relevant priority for the coming decades. Unfortunately, ancient herbarium samples have both time and conservation related DNA damages, besides exogenous DNA contamination, that make nucleic acid extraction and amplification challenging. Here, we present the results of DNA extraction, ITS2 amplification and Illumina MiSeq sequencing of 36 specimens from the Saccardo Mycological Herbarium that were collected in the late XIX century and assigned to the genus Peziza. High-throughput sequencing was chosen as an alternative to the conventional Sanger- and cloning-based methods to overcome the high fragmentation of the ancient DNA and the massive occurrence of non-target DNA from fungal contaminants. Our approach has permitted to assign ITS2 sequences to 23 out of the 36 specimens studied in this work, thus providing a univocal DNA sequence for those one century old samples. Furthermore, the ITS2 sequence analysis has permitted a taxonomic study of the samples that has resulted in a revaluation of 5 samples at the species level and 18 samples at genus or higher level. Our results highlight the possibility to apply the technique presented in this work also to the old and more precious type specimens in order to relate a DNA sequence to the species distinctive sample, coupling the traditional morphological description of the species with a DNA sequence.